Dampak Investasi Nikel China Di Indonesia Ditinjau Dari Perspektif Pembangunan Berkelanjutan dan Ekonomi Politik Hijau - Simatupang, Helga Yohana; Wulandari, Diah Ayu (Global and Policy Journal of International Relations, 2024)
ABSTRACT From the standpoint of sustainable development and green political economy, this study examines the effects of Chinese nickel investment in Indonesia. This study assesses how these investments affect politics, the economy, society, and the environment using qualitative methodologies and literature reviews. The primary conclusions demonstrate that Chinese nickel investment significantly boosts Indonesia's economy through exports, employment creation, and technology transfer. But there are also drawbacks, such as environmental harm, social unrest, and economic reliance, which need to be addressed. In order to reduce the adverse effects of investment, this study emphasizes the significance of enforcing stringent environmental regulations, boosting community involvement locally, and using green technology within the framework of sustainable development. Under the newly elected Indonesian president in 2024, the country's chances for Chinese nickel investment will be heavily influenced by geopolitical trends, government policies that encourage foreign investment, environmental effect mitigation, and strategic bilateral relationship management. In the end, while these investments provide significant economic opportunity, sustainability initiatives must be addressed to ensure long-term benefits for Indonesia. Keywords: Nickel, Indonesia, China Sustainable Development, Green Political Economy ABSTRAK Penelitian ini menganalisis dampak investasi nikel China di Indonesia dari perspektif pembangunan berkelanjutan dan ekonomi politik hijau. Dengan menggunakan metode kualitatif melalui studi pustaka, penelitian ini mengevaluasi dampak politik, ekonomi, sosial, dan lingkungan yang dihasilkan dari investasi tersebut. Temuan utama menunjukkan bahwa investasi nikel China memberikan kontribusi signifikan terhadap peningkatan ekonomi Indonesia, termasuk ekspor, penciptaan lapangan kerja, dan transfer teknologi. Namun, dampak negatif berupa kerusakan lingkungan, konflik sosial, dan ketergantungan ekonomi juga menjadi tantangan yang harus dihadapi. Dalam konteks pembangunan berkelanjutan, penelitian ini menyoroti pentingnya penerapan regulasi lingkungan yang ketat, peningkatan partisipasi masyarakat lokal, dan integrasi teknologi hijau untuk meminimalkan dampak negatif investasi. Prospek investasi nikel China di Indonesia pada kepemimpinan presiden baru Indonesia di tahun 2024 akan sangat tergantung pada kebijakan pemerintah yang mendukung investasi asing, mitigasi dampak lingkungan, pengelolaan hubungan bilateral secara strategis, serta tren geopolitik. Pada akhirnya, meskipun investasi ini membawa peluang ekonomi besar, upaya keberlanjutan harus diprioritaskan untuk memastikan manfaat jangka panjang bagi Indonesia. Kata Kunci: Nikel, Indonesia, China, Pembangunan Berkelanjutan, Ekonomi Politik Hijau